基于分层模糊优化的湿式多片离合器起步控制研究 - 闫光辉; 关志伟; 童敏勇 (Jixie chuandong)
According to the control theory of wet multi-plate clutch and starting process,taking full account of starting impact and sliding friction works,the starting process is analyzed and the control parameters of each starting process are selected.And then the hierarchical fuzzy optimization control strategy of clutch engagement occupation-empty ratio is proposed,which means the first analysis of starting intention,followed by initial occupation-empty ratio control,and finally to optimize occupation-empty ratio.Based on the control strategy,the control model and algorithm of hierarchical fuzzy optimization is designed.After vehicle simulation and compare with other control strategies,the results show that the strategy can effectively identify the driver’s starting intention,improve the smoothness of the wet clutch and reduce the starting impact and sliding friction works.